Investigashion of copper-alluminum contact pair surface obtained by plasmodynamic method; International Congress on Energy Fluxes and Radiation Effects (EFRE-2014) - Kolganova J. L. Julia Leonidovna; Sivkov A. A. Aleksandr Anatolyevich; Saigash A. S. Anastasiya Sergeevna; Shanenkov I. I. Ivan Igorevich (2014, 2014)
Title screen